"All that appears possible now is to mitigate as much as possible the trials of their closing years"1: Alfred Deakin's Attitudes to Aboriginal Affairs. (2nd May 2018) - Cahir, Fred; Tout, Dan
Abstract : This article examines Alfred Deakin's attitudes towards, and impacts upon, Aboriginal people during the period 1880–1910, drawing on newspaper articles and parliamentary debates as principal source materials. The discussion begins by charting the long, influential and often positive relationships Deakin had with several Aboriginal communities during a period as a Victorian MLA between 1881 and 1884. It then proceeds to document Deakin's extraordinary descent into paternalism and racially‐based fatalism which pervaded his later association with Aboriginal affairs whilst Victoria's Chief Secretary (1886–1890), Victorian MLA for Essendon and delegate to Federal conventions (1890–1900), as the Federation debates took shape. And finally, the article outlines the attitudes Deakin expressed towards Aboriginal people in his various post‐Federation political roles, including Attorney‐General, Prime Minister and Minister for External Affairs. In doing so, the discussion draws out the connections between Deakin's advocacy of a white Australia and his attitudes towards Aboriginal Australia, and demonstrates the extent to which the creation of a new nation both informed and responded to socio‐racial ideologies that mandated the exclusion of non‐white identities from the nation‐to‐come.